The structure of cognitive and non-cognitive impairment in patients with hallucinatory-paranoid disorders in mixed dementia - Shevchenko-Bitensky, Konstantin V. (Psychiatry, Neurology and Medical Psychology, 2020)
The aim of the study was to determine the specifics of cognitive impairment and clinic-psychopathological characteristics in patients with hallucinatory-paranoid disorders in mixed dementia.In study involved 72 patients with hallucinatory-paranoid disorders in mixed dementia (main group) and 61 patients with mixed dementia without psychotic disorders (control group).To achieve the goals and objectives of the study a comprehensive approach was used, which was implemented using the following research methods: the clinic-psychopathological method (a structured interview conducted as part of the clinical, phenomenological and psychopathological approaches in psychiatry), elementary neuropsychological studies of the main cognitive functions of patients (compilation of pictures, understanding of stories and plot pictures, establishing a sequence of events, classification, elimination of excess, highlight significant features, search for analogies, definition and comparison of concepts, formation of artificial concepts, selection antonyms words), held in a structured interview; Mini-Mental State Examination (MMSE) short mental state assessment scale; Montreal Cognitive Assessment Scale (MoCa); Behavioral Disorders Scale (BEHAVE-AD) and non-cognitive sections of the Alzheimer's Disease Rating Scale (ADAS-Non Cog). As a result of the study, features of cognitive impairment in mixed dementia with hallucinatory-paranoid disorders, which included: decreased concentration, impaired praxis, gnosis, delayed reproduction, counting skills, thinking (motivational, operational components of thinking and criticality) and orientation in one's own personality. The psychopathological features of hallucinatory-paranoid disorders in the structure of mixed dementia were determined, which included: delusions about dishonesty of others, hallucinations, disorders of the depressive spectrum, vagrancy, aimless activity (cognitive bulimia), inappropriate behavior, circadian rhythm disturbance, fear of being left alone.The distinguished features must be taken into account in the process of diagnosis and treatment of patients with hallucinatory-paranoid disorders in mixed dementia.